The Role of the Government in Improving the Performance of the Tourism Industry in Bali - I Gde Wedana Arjawa; Putu Ayu Sita Laksmi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aims to explore the influence of the government's role in improving tourism performance in Bali using a quantitative approach. This research method collects and analyzes numerical data to answer research questions and test hypo theses. The population of this study is 2,944 tourism business people in Bali, using the Slovin formula, a sample of 97 respondents with a margin of error of 10 percent was obtained. Primary data was collected through a survey method using a questionnaire. The research lasted for three months, with data processing and analysis using PLS software. The results of the study show that the role of the government has a significant influence on the performance of the tourism industry in Bali. This study provides an in-depth understanding of the cause-and-effect relationship between the variables studied and provides important insights for government policies in improving the tourism sector in Bali